Pengaruh Ketrampilan Wirausaha, Inovasi Produk, Dan Kreativitas Terhadap Perkembangan Usaha Sportwear & Clothing: (Studi pada Philosophy Industries Kecamatan Muntilan, Kabupaten Magelang) (Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2022)
Purpose- This study aims to prove the effect of entrepreneurial skills, product innovation and creativity on business ventures at Philosophy Industries.Methodology-This research was conducted on customers of Philosophy Industries. The sample in this study were 97 respondents who were customers of Philosophy Industries. Data was collected by means of a questionnaire that was distributed online to Philosophy Industries customers.Findings-The results showed that the entrepreneurial skill variable had a positive effect on business ventures at Philosophy Industries as evidenced by the t-count value of 3.194 > t table 1.66123 with a significance of 0.002 t table 1.66123 with a significance of 0.000 t table 1.66123 with a significance of 0.000